PERANAN TUAN GURU HAJI AHMAD SEBAGAI TOKOH PENDIDIKAN ISLAM DI KABUPATEN BENGKALIS (1924-1959) - Sulis Ratna Ayu; Isjoni Isjoni; Bunari Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this research is to find out the life history of Mr. Guru Haji Ahmad, to know the role of Mr. Guru Haji Ahmad in the field of Islamic education development, to find out the teaching methods set in the development of Islamic education, to find out the obstacles in spreading Islamic education, to find out social activities in the community in Bengkalis, to find out awards from the Bengkalis Regency government. The results of this study are Mr. Guru Haji Ahmad as a figure of Islamic education succeeded in establishing Mustaqin mosque in Pangkalan Batang Village, establishing a Madrasah school in Bangkit Parit, and establishing a pesantern named Al-khariyah. The method used in this study is qualitative and data obtained from interviews coupled with data set from books and data files obtained in their own language. As for the place of research in writing this scientific work is Bengkalis. Data collection techniques used are, documentation, interviews, observations, literature related to the role of the teacher Tuan Haji Ahmad as an Islamic education figure. Key Words: Mr. Guru Haji Role